Transcriptome Analysis Reveals the Potential Role of Long Non-coding RNAs in Mammary Gland of Yak During Lactation and Dry Period - Wu, Xiaoyun; Zhou, Xuelan; Xiong, Lin; Pei, Jie; Yao, Xixi; Liang, Chunnian; Bao, Pengjia; Chu, Min; Guo, Xian; Yan, Ping (Frontiers in Cell and Developmental Biology, 2020)
The mammary gland is a remarkably dynamic organ of milk synthesis and secretion, and it experiences drastic structural and metabolic changes during the transition from dry periods to lactation, which involves the expression and regulation of numerous genes and regulatory factors. Long non-coding RNA (lncRNA) has considered as a novel type of regulatory factors involved in a variety of biological processes. However, their role in the lactation cycle of yak is still poorly understood. To reveal the involved mechanism, Ribo-zero RNA sequencing was employed to profile the lncRNA transcriptome in mammary tissue samples from yak at two physiological stages, including lactation and dry period. Notably, 1,599 lncRNA transcripts were identified through four rigorous steps and filtered through protein-coding ability. A total of 50 lncRNAs showed significantly different expression between two stages. Accordingly, the results of qRT-PCR were consistent with that of the transcriptome data. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses indicated that target genes of differentially expressed lncRNAs (DELs) were involved in pathways related to lactation, such as fatty acid biosynthesis, insulin signaling pathway, PI3K-Akt signaling pathway, etc. By comparing the positional relationship between DELs and quantitative trait loci (QTL), we found that several DELs (such as LNC_000473) could be used as candidate markers for milk yield and quality traits. Finally, we constructed a lncRNA-gene regulatory network containing some well known candidate genes for milk yield and quality traits. This is the first study to demonstrate a global profile of lncRNA expression in the mammary gland of yak. These results contribute to a valuable resource for future genetic and molecular studies on improving milk yield and quality, and help us to gain a better understanding of the molecular mechanisms underlying lactogenesis and mammary gland development of yak.